Management of Waqf Assets in Malaysia - Zunaidah Ab Hasan; Azhana Othman; Khalilah Ibrahim; Mohd Ab Malek Md Shah; Abd. Halim Mohd Noor (International Journal of Nusantara Islam, 2015)
Waqf is one of the main mechanism in providing support for the development to all levels of the ummah more so for the underprivileged. Waqf institutions in Malaysia are under the jurisdiction of the 14 states rather than the Federal government. This paper reviews the development of waqf in Melaka, one of the states in Malaysia. It discusses a brief historical background, function and legal aspects of waqf matters. A brief information on the structure and administration of waqf in Melaka, Baitulmal is responsible for the sake of administering and managing such waqf assets in Melaka is also presented. This study is also concerned with examining of the current situation of development waqf asset; which is known as waqf saham in Melaka through the record by Majlis Agama Islam Melaka (MAIM). Yet, it is undeniably true that some challenges and impediments pertaining to the issues of developing waqf assets; inter alia, lack of fund and expertise, poor documentation and the record value of waqf property and others.